Using EuroForMix to analyse complex SNP mixtures, up to six contributors. (December 2017) - Bleka, Øyvind; Eduardoff, Mayra; Santos, Carla; Phillips, Chris; Parson, Walther; Gill, Peter
Abstract: A series of two- and three-person mixtures of varying dilutions were prepared and analysed with Life Technologies' HID-Ion AmpliSeq™ Identity Panel v2.2 using the Ion PGM™ massively parallel sequencing (MPS) system. From this panel we used 134 autosomal SNPs. Using the reference samples of three donors, we evaluated the strength of evidence with likelihood ratio (LR) calculations based on a quantitative model (EuroForMix) and compared the results with a previous study based on a qualitative model (LRmix). Taking account of the "peak height" information, by substituting 'sequence read' coverage values from the MPS data for each SNP allele, greatly improves the discrimination between true and non-contributors.